Análise da contaminação e degradação do óleo lubrificante e desgaste de um motor Ottolizado alimentado por biogás - Bertinatto, Rovian (2014)
The implementation of digesters for waste material treatment in rural properties, as well as the use of the biogas that is generated on the making of mechanical energy, has increased and alongside with it the necessity of understanding the influence of this fuel in internal combustion engines. This study aims to analyze the filtered biogas influence on contaminating and degrading the lubricating oil and the engine. Lubricating oil samples were collected on every 75 hours of engine operation, and, after they had been correlated among themselves and with new oil samples, it was possible to determine the elements that contaminate and degrade the engine after hours of engine working. Therefore, it was possible to notice that the hydrogen sulphide influences the lubricating oil and engine performance. Among the metals it was possible to identify that the copper concentration exceeded the maximum recommended levels, and the elevation of its concentration was related to the elevation of lead and tin, mainly after 375 Hm. As for the additives, the magnesium variation levels affected the lubricant perfomance. By monitoring the quality of the lubricant is possible to increase the oil change interval in 50%, which results in a 33.3% save regardomg the lubricant cost every worked hour